Analysis of Junior High School Students’ Misconceptions Based on Constructivism Theory in Solving Numeracy Literacy Problems - Rahmaniyah, Zahra; Ihsanudin, Ihsanudin (AlphaMath : Journal of Mathematics Education, 2024)
This study aims to use constructivist principles to find out how misunderstandings arise when solving arithmetic problems among students of grade 7 C of SMPN 2 Ciruas and to identify the factors responsible for them so that this problem can be presented to students and teachers as a reference for more effective learning. The subjects of this study were students of grade 7 C with high, medium and low comprehension skills. This study is qualitative and uses descriptive methods. It uses test instruments in the form of AKM sample questions and interview guides related to constructivist principles. The data analysis techniques used are data reduction, data display and inference. The results of this study explain the misunderstandings that students, especially those with low comprehension, experience when presented with numerical problems in a mathematical format. According to constructivist theory, factors that cause misunderstandings include: 1) lack of additional study time; 2) poor prior knowledge; 3) lack of understanding of the problem; 4) not taking an active role in the classroom; and 5) incorrect interpretation of the problem.